2012
DOI: 10.1126/science.1225967
|View full text |Cite
|
Sign up to set email alerts
|

Akt-Mediated Regulation of Autophagy and Tumorigenesis Through Beclin 1 Phosphorylation

Abstract: Aberrant signaling through the class I phosphatidylinositol 3-kinase (PI3K)-Akt axis is frequent in human cancer. Here we show that Beclin 1, an essential autophagy and tumor suppressor protein, is a target of the protein kinase Akt. Expression of a Beclin 1 mutant resistant to Akt-mediated phosphorylation increased autophagy, reduced anchorage-independent growth, and inhibited Akt-driven tumorigenesis. Akt-mediated phosphorylation of Beclin 1 enhanced its interactions with 14-3-3 and vimentin intermediate fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
532
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 639 publications
(564 citation statements)
references
References 21 publications
22
532
2
Order By: Relevance
“…For instance, it could act as a switch that controls a major cellular energy consumer, mTORC1, and a major energy producer, Akt. But also could have an important role to inhibit autophagy [47][48][49][50] which is an important process to prevent autophagy-mediated cell death. 47,51 Cytokine-driven autophagy has been observed in several pathological conditions including atherosclerosis, 52 myopathy 53 and arthritis, 54 which has been linked to TNFα and IFNγ presence.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it could act as a switch that controls a major cellular energy consumer, mTORC1, and a major energy producer, Akt. But also could have an important role to inhibit autophagy [47][48][49][50] which is an important process to prevent autophagy-mediated cell death. 47,51 Cytokine-driven autophagy has been observed in several pathological conditions including atherosclerosis, 52 myopathy 53 and arthritis, 54 which has been linked to TNFα and IFNγ presence.…”
Section: Discussionmentioning
confidence: 99%
“…39 Wang et al and Wei et al found that both EGFR (epidermal growth factor receptor) and AKT can individually regulate the activity of autophagy by phosphorylating BECN1. 31,40 Kim et al also showed that AMPK phosphorylates BECN1 S91/S94 (S90/S93 in human) to induce autophagy. 26 These 2 sites do not correspond to classical AMPK phosphorylation motifs.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Because AMPK is a protein serine/threonine kinase, we hypothesized that AMPK may phosphorylate BECN1 to initiate autophagy. Thus, we first tested whether AMPK could interact with BECN1.…”
Section: Ampk Phosphorylates Becn1mentioning
confidence: 99%
“…112 Of note, BECN1 is an important downstream target of AKT, which inhibits autophagy, and aberrant BECN1 phosphorylation by AKT is implicated in tumorigenesis. 133 In this scenario, AKT-mediated phosphorylation of BECN1 increases the binding of BECN1 with YWHA/14-3-3 proteins, which tethers BECN1 to the intermediate filament protein VIM/vimentin, leading to the suppression of autophagy. 133 Thus, AKT modulates the indirect interaction of BECN1 with intermediate filaments, mirroring the AMBRA1-regulated subcellular localization of BECN1-PIK3C3 to another kind of cytoskeleton, microtubules (to be discussed below).…”
Section: Regulation Of Autophagy By Pik3c3 Via Becn1mentioning
confidence: 99%
“…133 In this scenario, AKT-mediated phosphorylation of BECN1 increases the binding of BECN1 with YWHA/14-3-3 proteins, which tethers BECN1 to the intermediate filament protein VIM/vimentin, leading to the suppression of autophagy. 133 Thus, AKT modulates the indirect interaction of BECN1 with intermediate filaments, mirroring the AMBRA1-regulated subcellular localization of BECN1-PIK3C3 to another kind of cytoskeleton, microtubules (to be discussed below). 80 In addition, DAPK1 (death-associated protein kinase 1) phosphorylates BECN1 at its BH3 domain and releases BECN1 from BCL2, which promotes autophagy.…”
Section: Regulation Of Autophagy By Pik3c3 Via Becn1mentioning
confidence: 99%